Nanostructuring for Nitride Light-Emitting Diodes and Optical Cavities - Li, Kwai Hei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book describes the design and fabrication of novel nanostructures in III-nitride material systems. It introduces an inexpensive and ultra-efficient nanopatterning method - nanosphere lithography (NSL) - used to develop diversely functional nanostructures, including clover-shaped photonic crystals, nanorings, and nanolenses. Furthermore, the research findings previously distributed in various international scientific journals and conference papers are brought together and methodically presented in a unified form. The book is of interest to postgraduate students, university researchers, R&D engineers and scientists in the fields of nanoelectronics, optoelectronics and photonics.
Introduction -- Background -- III-Nitride light-emitting diodes with photonic crystal structures -- Whispering gallery mode lasing from sphere-patterned cavities -- 1-μm Micro-lens Array on Flip-chip LEDs -- Optical and Thermal Analyses of Thin-film Hexagonal Micro-mesh Light-emitting Diodes -- Conclusion and Future Work.
Keywords: Optical materials; Lasers; Microtechnology; Microelectromechanical systems; Optical Materials; Laser; Microsystems and MEMS